A Systematic Review on Integrating SSI into Science Education: Its Impact on 21st Century Skills (2014-2024) - Sari, Dwi Retno; Saputro, Sulistyo; Sajidan, Sajidan (Educational Studies and Research Journal, 2025)
The Socio-Scientific Issues (SSI)-based learning approach has been recognized as an effective method in science education to develop students' essential skills. This study aims to explore the impact of SSI learning on six key skills: scientific literacy, critical thinking, problem-solving, social awareness and responsibility, argumentation, and collaborative and communicative skills. This research method uses the PRISMA guideline to review relevant literature. Articles were obtained from the Scopus database with the keywords "socio-scientific issues," "socioscientific issues," and "science education" which were limited to publications from 2014 to 2024. The results of the analysis of 46 articles showed that SSI-based learning can improve students' scientific literacy through the context of global issues, such as climate change and renewable energy, which provide a deeper scientific understanding. This learning also hones students' critical thinking skills by encouraging evaluation of evidence and analysis of multiple perspectives. In addition, the SSI approach encourages problem-solving skills by inviting students to find innovative solutions to environmental and health issues, as well as increasing their social awareness and responsibility. Students also develop argumentation skills through discussions and debates, as well as collaborative skills through SSI-based projects. In conclusion, SSI learning not only enriches students' scientific understanding but also prepares them with essential skills to face global challenges in the modern era.